Monitoring the fetal heart for the assessment of fetal wellbeing. Systematic reviews of the evidence and the design, conduct and preliminary findings of a multi-centre randomised trial THE ADCAR TRIAL - Smith, Valerie (Trinity College (Dublin, Ireland). School of Nursing & Midwifery, 2010)
The assessment of fetal wellbeing throughout pregnancy, labour and birth, is essential in achieving maternity care that optimises fetal outcomes. Monitoring of the fetal heart rate (FHR), using either intermittent auscultation (1A) (i.e. listening to the FHR at regular intervals using a Pinard stethoscope or hand-held Doppler device) or electronic fetal monitoring (EFM), (i.e. recording of the FHR by a special electronic machine) is one practice central to the assessment of fetal wellbeing. Admission cardiotocography (ACTG), a form of EFM, is a routine screening test consisting of a twenty minute electronic recording of the FHR and uterine activity performed on women on admission to the labour ward or labour assessment room with signs of possible labour. The premise for the use of ACTG is that it may identify those babies, from the onset of possible labour, who might benefit from continuous EFM during labour.
Keywords: Nursing and Midwifery, Ph.D.; Ph.D. Trinity College Dublin